2020
DOI: 10.1097/qad.0000000000002578
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HIV on the survival of hepatocellular carcinoma in hepatitis C virus-infected patients

Abstract: Background: Previous studies have suggested that hepatocellular carcinoma (HCC) has an aggressive presentation and a shorter survival in people with HIV (PWH). This could be due to later diagnosis or lower rates of HCC treatment, and not to HIV infection itself. Aim: : To assess the impact of HIV on HCC survival in hepatitis C virus (HCV)-infected patients. Methods: Multicenter cohort study (1999–2018) of 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Our data adds to a growing number of studies reporting an adverse effect of HIV on HCC outcomes, several of which have reported similarly reduced survival among PLH and an independent effect of HIV on mortality [14,[20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The mechanisms underlying the effects of…”
Section: Discussionmentioning
confidence: 56%
“…Our data adds to a growing number of studies reporting an adverse effect of HIV on HCC outcomes, several of which have reported similarly reduced survival among PLH and an independent effect of HIV on mortality [14,[20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The mechanisms underlying the effects of…”
Section: Discussionmentioning
confidence: 56%
“…In the study by Merchante et al, [ 26 ] 1- and 3-year survival was 50% and 31% in PLWH and 69% and 34% in those without HIV ( P = 0.16) with 33% of HIV-infected patients showing BCLC = 0/A vs. 56% of HIV uninfected. In our group of PLWH, we found a higher cumulative probability of survival at one year (68%) with a similar prevalence of BCLC = 0/A (34%).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning survival, clinical studies have demonstrated that HCC/PLWH can obtain a satisfactory survival rate after treatment [ 6 , 8 , 49 ]. Although 18 (43.9%) PLWH received non-curative IT (chemo/radioembolization) as their first therapy, we had a good overall survival because approximately 50% of our participants were alive after 5 years from their HCC diagnosis.…”
Section: Discussionmentioning
confidence: 99%